Analisis Korelasi Statistikal Fenomena Kejadian ENSO dan MJO terhadap Kondisi Klimatologis di Provinsi Riau - Muhammad Ansori Hasibuan; Dwiki Anugerah Atmojo; Huda Wahyujati; Farhan Nul Hakim; Giarno Giarno (Jurusan Pendidikan Geografi Universitas Negeri Manado, 2023)
El Nino-Southern Oscillation (ENSO) and Madden-Julian Oscillation (MJO) events are significant factors in the global climate system. Riau Province, located on the island of Sumatra, is highly influenced by these phenomena. This study collects climate data from weather stations in Riau Province and reliable sources for ENSO and MJO indices. Statistical analyses, including correlation and regression, are employed to determine the relationship between climate variables in Riau Province and ENSO and MJO. Based on data from 2001-2019, the results reveal a medium category correlation value (r = 0.452) with coefficients a and b of 1.288 and 0.089, respectively. The increased MJO value contrasts with the rainfall during the 2001-2019 timeframe. This information serves as a reference for understanding the ENSO and MJO phenomena in the Riau region.